2014
DOI: 10.1021/nl404228z
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Epitaxial Electrodeposition of Single-Crystalline Germanium Nanowires at the Wafer Scale from an Aqueous Solution

Abstract: Direct epitaxial growth of single-crystalline germanium (Ge) nanowires at room temperature has been performed through an electrodeposition process on conductive wafers immersed in an aqueous bath. The crystal growth is based on an electrochemical liquid-liquid-solid (ec-LLS) process involving the electroreduction of dissolved GeO2(aq) in water at isolated liquid gallium (Ga) nanodroplet electrodes resting on single-crystalline Ge or Si supports. Ge nanowires were electrodeposited on the wafer scale (>10 cm(2))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 34 publications
(53 reference statements)
6
80
1
Order By: Relevance
“…10,13,14 In general, the data shown here further emphasize that ec-LLS can be a synthetic materials method at the micro-, meso-, and macro-length scales. However, with liquid Ga or GaIn microdroplets, the growing Ge crystal(s) push the liquid metal nano/microdroplet away from the surface because nucleation and crystal growth occur preferentially at the interface between the liquid metal droplet and the support substrate.…”
Section: D504supporting
confidence: 58%
See 1 more Smart Citation
“…10,13,14 In general, the data shown here further emphasize that ec-LLS can be a synthetic materials method at the micro-, meso-, and macro-length scales. However, with liquid Ga or GaIn microdroplets, the growing Ge crystal(s) push the liquid metal nano/microdroplet away from the surface because nucleation and crystal growth occur preferentially at the interface between the liquid metal droplet and the support substrate.…”
Section: D504supporting
confidence: 58%
“…13,14 There are no previous reports on whether the same is achievable with small Hg droplets, i.e. at volumes 10 10 times smaller than our previous investigation with Hg as an ec-LLS electrode/medium.…”
mentioning
confidence: 61%
“…In fact, we showed both homoepitaxy and heteroepitaxy in ec-LLS of Ge nanowires. 37 In these experiments, the liquid Ga nanodroplets were always observed on the tip of the Ge nanowire. For longer ec-LLS nanowire experiments, stacking faults were observed that caused kinking.…”
Section: Ec-lls Synthesis Of Crystalline Group IV Semiconductorsmentioning
confidence: 89%
“…For longer ec-LLS nanowire experiments, stacking faults were observed that caused kinking. 37 Notably, all of the nanowires across a given film showed kinking at essentially the same position (Figure 5c), implying that the stacking faults formed consistently and simultaneously for each nanowire. A consequence of the stacking faults was an abrupt change in growth direction within the [111] family.…”
Section: Ec-lls Synthesis Of Crystalline Group IV Semiconductorsmentioning
confidence: 91%
“…5,[35][36][37] More recently, an electrochemical electrolyte-liquid-solid analog has been demonstrated for growth of Ge nanowires. [38][39][40] In another approach nanowire growth of metallic nanostructures capitalizes on the intrinsic or additive engineered anisotropic energetics and/or growth kinetics on different crystal facets. 21,41 For example, adsorption of anions or dilute metal ion additives, via under potential deposition (upd), enables fabrication of structures such as Au nanospikes of moderate aspect ratio using a Pb additive 42,43 and highly faceted, moderately elongated dendrite-like grains using Tl as an additive 44 on unpatterned substrates.…”
mentioning
confidence: 99%